OP0012-HPR Creation of the first digital training designed for patients with rheumatoid arthritis by patient organisation in rheumatology. (12th June 2018) - Trope, S.; Cohen, J.-D.; Beauvais, C.; Dugoua Jacques, G.; Poivret, D.; Saraux, A.; Vacher, D.; Barkatz, H.; Lacoste, P.; Weill, V.; Thibaud, G.
Abstract : Background: People with chronic conditions face the disease more effectively when they develop psychosocial skills and self-care. Health authorities thus recommend the organisation of therapeutic patient education (TPE)… suffering from different limitations. Objectives: A patient organisation had the idea to develop a digital training solution, accessible everywhere, complementary to TPE, for patients with rheumatoid arthritis. Methods: The choice was made for an online training program such as Massive Open Online Courses (MOOC). A preliminary survey was carried out among the patients via an electronic questionnaire via social networks and an emailing to the organisation members. A steering committee (COPIL) made up of representatives of the patients' association, expert patients and rheumatologists with the support of a specialised agency, determined the timetable, the educational objectives, the contents, the speakers and the evaluations. Results: The initial investigation was stopped at 100 responses, obtained in 3 days. 85, 9% planned to follow the MOOC on their computer, but to meet the needs of all, the device is responsive. 61% had never participated in a TPE program and 94% were interested in joining MOOC to learn new information about the disease (78.8%), treatments (71.7%), have expert views (67.7%), share experience with other patients (56.6%), and better live with the disease (50.5%). The MOOC: Using the Learning Management System platform drspoc.com, Intervention of the experts via videos and live courses, evaluation of the achievements and, during two annual sessions, tutoring by patients trained specifically. At the beginning and end of the session, learners are invited to answer different questionnaires (knowledge, skills, satisfaction). COPIL identified 15 experts (patient-experts, rheumatologists, occupational therapist, physiotherapist, nutritionist, social worker, psychologist, sexologist, nurse) who wrote the content of their speech. All texts have been validated by a pedagogical engineer and the director of the association. 215 people pre-registered during the month preceding the launch, 154 persons active and 446 posts shared during the first session. 217 pre-registered, 238 actives, 1 257 posts during the second sessions, tutored by peer patients with a dedicated training. Some participants were health care professionals and their extremely positive feedbacks prove the value in offering MOOC access to every people interested in. Conclusions: This is the first digital training strategy for people with rheumatoid arthritis. It proved to be useful to patients, offering an alternative or complement to TPE. It will be necessary to evaluate the impact of this MOOC on the quality of life of the patients and their perception on its usefulness after several sessions. We decided to propose an e-learning version without peer patient intervention and accessible at any time in addition to the MOOC version with a specific educational path. Acknowledgements: This project received an institutionnal grant from Abbvie, Biogen, Lilly, Nordic, Pfizer, Roche-Chugai, Sandoz, Sanofi. All medical and patient experts volunteers. Disclosure of Interest: None declared